Sekar Macapat Pocung: Study of Religious Values Based on The Local Wisdom of Javanese Culture - Saddhono, Kundharu; Pramestuti, Dewi (el Harakah: Jurnal Budaya Islam, 2018)
Javanese culture is a system of ideas which directs Javanese people’s attitude and behaviors. It contains local wisdom that has a great influence on their daily life. The research method employed in this study is descriptive qualitative by implementing content analysis approach. The data studied are the scripts of Sekar Macapat Pocung. Local wisdom has a highly philosopical meaning which enhances the tenacity of nations. Tembang Macapat is considered as a form of local wisdom in Javanese culture. Sekar Macapat Pocung is the eleventh popular meters of recited Javanese poem. Through the recited Javanese poem, Islamic religious values and noble values are delivered meaningfully. It becomes precept and inseparable part of Javanese people in leading religious and national life. Budaya Jawa merupakan suatu sistem yang menjadi pedoman bagi masyarakat Jawa dalam berperilaku dan bersikap. Di dalam budaya Jawa terdapat kearifan lokal sebagai pendorong yang kuat dalam kehidupan masyarakat Jawa. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pendekatan analisis isi. Data yang dikaji adalah naskah Sekar Macapat Pocung. Kearifan lokal budaya Jawa mengandung makna filosofis yang meningkatkan ketahanan nasional sebuah bangsa. Tembang Macapat termasuk wujud kearifan lokal budaya Jawa. Sekar Macapat Pocung adalah metrum kesebelas yang dikenal sebagai produk budaya berbentuk puisi Jawa kuno yang dilagukan. Melalui syair dalam tembang, nilai-nilai religus Islam dan pitutur bijak disampaikan penuh makna. Nilai-nilai religus Islam dan pitutur bijak dalam Sekar Macapat Pocung menjadi pegangan dan bagian hidup yang tak terpisahkan dari masyarakat Jawa dalam menjalani kehidupan beragama dan berbangsa.